Determining molecular orientation via single molecule SERS in a plasmonic nano-gap. Issue 44 (6th November 2017) - Marshall, Addison R. L.; Stokes, Jamie; Viscomi, Francesco N.; Proctor, John E.; Gierschner, Johannes; Bouillard, Jean-Sebastien G.; Adawi, Ali M.
Abstract : Through combining single molecule SERS measurements, DFT and FDTD calculations, the molecular orientation within the plasmonic nano-gap is recovered. Abstract : In this work, plasmonic nano-gaps consisting of a silver nanoparticle coupled to an extended silver film have been fully optimized for single molecule Surface-Enhanced Raman Scattering (SERS) spectroscopy. The SERS signal was found to be strongly dependent on the particle size and the molecule orientation with respect to the field inside the nano-gap. Using Finite Difference Time Domain (FDTD) simulations to complement the experimental measurements, the complex interplay between the excitation enhancement and the emission enhancement of the system as a function of particle size were highlighted. Additionally, in conjunction with Density Functional Theory (DFT), the well-defined field direction in the nano-gap enables to recover the orientation of individual molecules.